Valuable resources recovery from palm oil mill effluent (POME): A short review on sustainable wealth reclamation - Saifullahi Shehu Imam; Sadiq Sani; Muhammad Mujahid; Rohana Adnan (Waste Management Bulletin)
Palm oil mill effluent (POME) is a substantial by-product generated in the palm oil industry that has traditionally been regarded as waste due to its high pollutant content. However, recent advances emphasize the possibility of recovering valuable resources from POME, which would contribute to environmental sustainability and economic benefits. This made POME treatment the subject of numerous investigations. Various methods, mostly biological, have evolved over the past few years for the successful valorization of POME to produce useful resources including biofuels (biohydrogen, biogas, bioacetone, biobutanol, bioethanol, biohythane etc.), value-added chemicals (enzymes, volatile fatty acids, citric acid, carotenes, lipids etc.), nutrients (micronutrients, macronutrients), pesticides, solvents, and adsorbents. The current review’s objective is to summarize the possible approaches for conversion of POME waste to wealth with some outlooks. By transforming waste into valuable resources, the palm oil sector can improve its sustainability, minimize environmental footprints, and establish new revenue streams.